Cultural Mediation in Tourism: Online Promotional Travel Guides as a Case Study - Souhail, Asma; Darir, Hassane (International Journal of Language and Literary Studies, 2023)
In tourism, mediation refers to the assistance of tourists in their journey. In other words, mediation occurs when the mediator presents the culture of a place to potential tourists while making sure that the cultural elements are clear enough for the tourists to grasp. Culture is an embedded element in tourism promotion. Hence, the mediator must be well grounded in the culture in order to adequately transmit it to the tourists discovering it for the first time. The study relies on excerpts extracted from online travel guides, which have become a widely used means of promotion in “post-pandemic” travel due to their innovative promotional approaches, i.e., considering safety measures. Following a qualitative approach, a comparative study is conducted to explore how culture is “mediated” through four international online travel guides. The focus is on the element of Moroccan culture and the tools employed when it is presented to the English readership.